2013
DOI: 10.1007/s11095-013-1191-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide-Mediated Generation of Hybrid Nanoparticles for Improved Bioavailability of Protein Kinase Inhibitors

Abstract: PurposeA versatile methodology is demonstrated for improving dissolution kinetics, gastrointestinal (GI) absorption, and bioavailability of protein kinase inhibitors (PKIs).MethodsThe approach is based on nanoparticle precipitation by sub- or supercritical CO2 together with a matrix-forming polymer, incorporating surfactants either during or after nanoparticle formation. Notably, striking synergistic effects between hybrid PKI/polymer nanoparticles and surfactant added after particle formation is investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Yasuji et al reviewed particle design of poorly water-soluble APIs using supercritical fluid technologies [14]. Solid dispersion nanoparticles manufactured with hydrophilic polymers and surfactants using the SAS process significantly improved the solubility, dissolution, and oral bioavailability of poorly water-soluble APIs such as atorvastatin calcium, azithromycin, dutasteride, lercanidipine, nilotinib, valsartan, tadalafil and telmisartan [15,16,17,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Yasuji et al reviewed particle design of poorly water-soluble APIs using supercritical fluid technologies [14]. Solid dispersion nanoparticles manufactured with hydrophilic polymers and surfactants using the SAS process significantly improved the solubility, dissolution, and oral bioavailability of poorly water-soluble APIs such as atorvastatin calcium, azithromycin, dutasteride, lercanidipine, nilotinib, valsartan, tadalafil and telmisartan [15,16,17,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Koehl et al [ 139 ] explored the potential of lipid vehicles to improve the bioavailability of hydrophobic drugs such as Nilotinib, comparing a chase-dosing approach and lipid suspensions. To improve the dissolution kinetics, gastrointestinal absorption and bioavailability of some TKIs (including Nilotinib), Jesson et al [ 140 ] prepared hybrid NPs, consisting of amorphous TKI embedded in a polymer matrix; these nanosystems displayed an increase in Nilotinib release rate in both simulated gastric fluid and intestinal fluid, particularly when surfactants are present on the hybrid nanoparticle surface. The prepared hybrid NPs represent a promising approach to improve drug dissolution rate, gastrointestinal absorption and bioavailability following oral administration [ 140 ].…”
Section: Nanoparticles Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…[1][2][3][4][5] The solution-enhanced dispersion by supercritical fluids (SEDS) process is an interesting and powerful technique for producing protein nanoparticles with a narrow particle size distribution. [4][5][6][8][9][10]] Surprisingly, protein nanoparticles fabricated with supercritical fluids retain their biological activity and native structure upon redissolution in aqueous solution. [1,[4][5][6][8][9][10] Pyo reported that two shapes of insulin nanoparticles can be produced using the SEDS process from dimethyl sulfoxide (DMSO) and ethanol (EtOH) solutions without the use of additives.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][8][9][10]] Surprisingly, protein nanoparticles fabricated with supercritical fluids retain their biological activity and native structure upon redissolution in aqueous solution. [1,[4][5][6][8][9][10] Pyo reported that two shapes of insulin nanoparticles can be produced using the SEDS process from dimethyl sulfoxide (DMSO) and ethanol (EtOH) solutions without the use of additives. [5] DMSO and EtOH were used to assist the supercritical carbon dioxide extraction of water from the aqueous protein solution.…”
Section: Introductionmentioning
confidence: 99%